A thermal stress analysis of fluid–structure interaction applied to boiler water wall. Issue 6 (6th August 2020) - Zhang, Zhenrong; Yang, Zong; Nie, Huichao; Xu, Ligang; Yue, Junfeng; Huang, Yaji
Abstract: Fluid–structure interaction (FSI), the combination of computational fluid dynamics and computational solid mechanics, is considered as a procedure to determine the stress or strain of the solid under the influence of flow movement. Common parameters such as pressure and temperature that existed in the fluid solver and solid solver are the core factors of date communication in FSI. This work investigated the thermal stress and deformation distribution of the vapor segment of the water wall by numerical simulation under two typical conditions of the 660‐MW boiler. The ideal condition and the case with the oxide scale inside were compared to realize the peculiarity of parameter distribution. The results revealed that the peak temperature of water wall was 812.51 K and the maximum deformation was 19.286 mm under ideal condition. Thermal stress of the water wall in the central region was 70–90 Mpa under ideal condition. The "double‐wave peak" temperature tendency on the fire side was presented with both boundary conditions. However, in terms of the scaling condition, the temperature of water wall escalated result from the heat transfer deterioration. Besides, the scale layer hindered the free expansion of the pipe bank and restrained the deformation of the membrane water wall result in the increase of thermal stress and the decrease of reference deformation.